Role of nanoparticle in PNN-PZT/Ag nanocomposite - Chung, HT; Cheon, DS; Kim, CS (ELSEVIER SCIENCE BV, 2005)
In the present work. we studied the role of nanoparticles in ferroelectric/silver composites, in which silver is the secondary particle. The ferroelectric system that we adapted was PNN-PZT. To make the PNN-PZT/silver nanocomposite, we hot-pressed the composite at 850 degreesC/2 h. A nanocomposite could be obtained with <0.5 vol.% of silver. We found that silver nanoparticles more effectively relieved the internal stresses than microparticles, which affected lattice parameter and transition temperature of the nanocomposites. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: MICROSTRUCTURE; FABRICATION; COMPOSITES; REDUCTION; BEHAVIOR